1988
DOI: 10.1136/jcp.41.1.85
|View full text |Cite
|
Sign up to set email alerts
|

Campylobacter associated gastritis in patients with non-ulcer dyspepsia.

Abstract: SUMMARY Gastric biopsy specimens from 109 patients with non-ulcer dyspepsia were retrospectively examined. Sixty one patients had gastritis and there was a strong correlation with the presence of Campylobacter pyloridis. Ninety eight per cent were positive in large numbers for C pyloridis by histological examination or by culture, or both. Of 48 patients with normal histological results, 21 had evidence of C pyloridis by histological examination or culture, or both, but in small numbers. It is concluded that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
2

Year Published

1989
1989
2002
2002

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(24 citation statements)
references
References 20 publications
(3 reference statements)
1
21
0
2
Order By: Relevance
“…Also, HP appears to be closely associated with chronic active gastritis (91% of our cases) and its eradication in these cases is desirable. The benefits of eradicating HP patients with non-ulcer dyspepsia have not been fully established [5,27]. Non-ulcer dyspepsia was found in 95 cases in the current study (45.7%) and associated histologically proven gastritis was seen in 63 patients (66%).…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Also, HP appears to be closely associated with chronic active gastritis (91% of our cases) and its eradication in these cases is desirable. The benefits of eradicating HP patients with non-ulcer dyspepsia have not been fully established [5,27]. Non-ulcer dyspepsia was found in 95 cases in the current study (45.7%) and associated histologically proven gastritis was seen in 63 patients (66%).…”
Section: Discussionmentioning
confidence: 52%
“…During the last ten years, HP has rapidly gained recognition as an important etiologic factor in peptic ulcer disease [2,3], gastritis [4], and non-ulcer dyspepsia [5], and also has been found in healthy carriers [6].…”
mentioning
confidence: 99%
“…The system recommends that histopathologists make semiquantitative evaluations of gastritis, including the density of Helicobacter pylori in biopsy samples [1]. The density of H. pylori in such samples is correlated to the severity of gastritis [2,3]. The bacterial density of H. pylori in the stomach may be a predictive parameter for treatment success [4,5], and may be associated with bacterial virulence factors in ulcer pathogenesis [6].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of C. pylori in patients with NUD is 45 to 70% and the prevalence of gastritis is similar (68,77,109,110,126,127), suggesting possible involvement of the organism in the disease. One of the problems with assessing these data is that there is an age-related increase in the prevalence of the organism (43,50,92), and, thus, C. pylori is found in about 50% of asymptomatic individuals 50 to 60 years old.…”
Section: Nudmentioning
confidence: 92%
“…Other simpler stains have been suggested recently. These include the Giemsa (103) A number of different media have been used for recovering C. pylori, including 5 to 10% horse blood agar (24,38,98,104), 5 to 10% sheep blood agar (61,68,123,132), chocolate agar (10,14,60,77,80,109), Skirrow medium (24,104,110), and Thayer-Martin medium (10,34,98). A number of investigators found that using antibiotics in the medium to suppress contaminating bacteria was advantageous (19,24,38,61,98,132 Only minimal work has been conducted to establish which of these media is best for isolating the organism.…”
Section: Laboratory Diagnosismentioning
confidence: 99%